Sustainable urban designs integrating aboveground microclimates and underground heat islands: A systematic review and design strategies - Wen, Yueming; Zhang, Peiyi; Wei, Jinxi; Yu, Fei; Huang, Chengfang (Renewable & sustainable energy reviews, 2025)
Current theoretical models and analytical techniques in urban microclimates primarily concentrate on the ‘underlying surface’ spanning from the boundary of the urban canopy layer to ground level. However, they frequently neglect the impacts of underground spaces such as buildings, transportation, and utility tunnels, serving as heat sources affecting pedestrian thermal comfort, urban energy consumption, and geothermal energy. Moreover, idealised soil temperature models employed in numerical simulations fail to consider disturbances from aboveground and underground built environments. Consequently, this results in inaccuracies when predicting underground spaces' physical environment and energy consumption. First, this study systematically reviews aboveground microclimate and underground heat islands, summarising correlation mechanisms and key design highlights. Then, an environmental concept of the ‘underlying layer’ is proposed to expand the research scope to the boundary of the variable temperature soil layer, encompassing shallow underground spaces and accounting for underground heat islands. After that, this study discusses multi-scale and multi-process numerical simulation, spatial information modelling, energy balance models, and thermally disturbed soil temperature modelling. Finally, sustainable urban design approaches and strategies are discussed from functional layout, urban form, ground surface, and geothermal energy utilisation. This study bridges the gap in the physical environment and urban energy of aboveground-underground integration. It elucidates the practical needs and critical techniques of environmental modelling and prediction approaches, thereby enhancing urban design, energy conservation and carbon reduction in sustainable cities. [Display omitted] •A systematic review correlating microclimate and underground heat islands.•Interactions and elements between aboveground and underground environments.•The environmental concept and research techniques of the ‘underlying layer’.•Sustainable urban design strategies from physical environments and energy.